Mothers' sociodemographic factors and use of health professionals for child feeding advice - Eve House; Huilan Xu; Sarah Taki; Elizabeth Denney‐Wilson; Louise Baur; Li M. Wen (Wiley, 2024)
Abstract This study examined sociodemographic factors associated with mothers seeking child feeding advice from health professionals (HPs). Cross‐sectional analysis of survey data from linked randomized controlled trials was conducted. Surveys asked which sources of feeding information mothers used when their child was 6 months and 5 years old. Logistic regression was used to examine associations between sociodemographic characteristics and use of information from HPs. Here, 947 and 405 mothers completed 6‐month and 5‐year surveys, respectively. At 6 months, multiparous mothers were less likely to seek advice from child and family health nurses (CFHNs) (adjusted odds ratio [AOR]: 0.558, 95% confidence interval [95% CI]: 0.416-0.749) and other HPs (AOR: 0.706, 95% CI: 0.542-0.919), unmarried mothers were less likely to seek advice from other HPs (AOR: 0.582, 95% CI: 0.342-0.990). At 5 years, mothers with household income ≥$80,000 p.a. were less likely to seek advice from CFHNs (AOR: 0.514, 95% CI: 0.302-0.875) and working mothers less likely to seek advice from general practitioners (GPs) (AOR: 0.581, 95% CI: 0.374-0.905). Mothers born in Australia were less likely to seek information from CFHNs (AOR: 0.462, 95% CI: 0.257-0.833) and GPs (AOR: 0.431, 95% CI: 0.274-0.677). There was a greater likelihood that multiparous mothers (AOR: 2.114, 95% CI: 1.272-3.516) and mothers of children whose fathers had not attended university (AOR: 2.081, 95% CI: 1.256-3.449) had never sought advice from CFHNs, and that mothers who had not attended university (AOR: 1.769, 95% CI: 1.025-3.051), multiparous (AOR: 1.831, 95% CI: 1.105-3.035) and employed (AOR: 2.058, 95% CI: 1.135-3.733) mothers had never sought advice from other HPs. Understanding sociodemographic factors associated with seeking child feeding advice from HPs may inform priorities for engaging families in health promotion.